FUNCTIONAL RESTORATION OF THE SPINE: EFFECT OF A SUPPORT PROGRAM ON THE PHYSICAL PERFORMANCE OF THE SPINE OF LOW BALGIC DOCKERS IN THE AUTONOMOUS PORT OF LOME. - ALEGBEH, ES; AKPLOGAN, B; AZE, OSCAR DAGBEMABOU OLADOUNI; ADJENOU, KV; HOUNMENOU, A; GBATI, DKL; DANSOU, P (My University, 2015)
This study aims to evaluate the effect of a lumbar stretching program associated with electromyostimulation on the physical performance of low back pain spine Dockers of the Autonomous Port of Lomé. This is an intervention study conducted with 32 dock workers suffering from back pain. This sample was randomly divided into two groups (experimental and control) of 16 subjects. Physical tests and mobility of the spine, as well as assessing the degree of pain were made for each subject at operation (TO), after 4 weeks (Tl), at the end of the intervention (T2) and after three months from the end of the program. Statistical analysis was performed on PASW statistics v.18 (SPSS Inc., Chicago, IL, USA), with a significance level set at p <0.05. The average age of dockers included was 50.29 + 5.26 years. The results show a significant improvement in endurance flexor (p < 0, 0001) and flexor muscles of the spine (p < 0,0001), the spinal mobility (p < 0,007) and the degree of pain (p < 0,0001). The support program implementation seems beneficial in restoring key parameters of the subject LBP.
Keywords: dock; spine; back pain; care; electrostimulation